Analysis of cytomegalovirus UL97 drug resistance mutations in patients receiving Ganciclovir - Nkosi, Nokwazi Pearl (Division of Virology, 2018)
Introduction: Cytomegalovirus (CMV) drug resistance mutations, because of the widespread use of ganciclovir, have been widely reported in international literature, particularly in the post-transplant setting. However, a genotypic assay to detect CMV drug resistance is not available in South Africa and the prevalence of these mutations is therefore unknown. We aimed to document the prevalence and types of CMV UL97 mutations following exposure to ganciclovir in adult and paediatric oncology patients, transplant recipients and HIV-infected patients in the local tertiary level hospitals: Red Cross War Memorial Children's Hospital, Groote Schuur Hospital and Tygerberg Hospital. Methods: The study had two components, the first component being a retrospective cross-sectional study using stored extracted DNA from patients with serially elevated CMV viral load levels. Thirty-three samples were tested for this component. The second component was a prospective case series on patients who were referred by clinicians for genotypic testing in whom CMV drug resistance was suspected. Eight samples were tested for this component. The CMV UL97 gene was amplified by conventional nested polymerase chain reaction (PCR) and Sanger sequencing performed. Results: CMV UL97 mutations were identified in five of thirty-three (15%) retrospectively screened samples while the prospective testing of eight patient samples identified drug resistance mutations in three patients (38%). Overall 8/41 (20%) patients had CMV UL97 mutations. A trend of higher risk for development of drug resistance mutations among haematological oncology patients 7/23 (30%) compared to solid organ transplant recipients 1/10 (10%) was observed, however, this difference was not statistically significant (P=0.306). Conclusion: This study, the first of its nature in South Africa, identified the presence of CMV UL97 mutations conferring resistance to ganciclovir in the haematological oncology, primary immunodeficiency and solid organ transplant patients in the Western Cape. The assay successfully detected CMV UL97 drug resistance mutations in whole blood and cerebrospinal fluid clinical samples. Ongoing viral replication in the background of intensive immunosuppression and prolonged antiviral therapy selects for the emergence of CMV UL97 drug resistance mutations.